Implementation of Visual Media in Improving Understanding of Religious Education in Children in Group A Raudhatul Athfal Aman Sentosa Sekuduk Village - Sera Yuliantini; Ozy Anggrean (ADISAM PUBLISHER, 2023)
The purposes of this study are: 1) Describe the stages of implementing visual media in increasing understanding of religious education in children in group A Raudhatul Athfal Aman Sentosa Sekuduk village; 2) Describe the Obstacles in the Implementation of Visual Media in Improving Understanding of Religious Education in Children in Group A Raudhatul Athfal Aman Sentosa Sekuduk Village; 3) Describe the Teacher's Efforts to Overcome Obstacles to the Implementation of Visual Media in Improving Understanding of Religious Education in Children in Group A Raudhatul Athfal Aman Sentosa Sekuduk Village. This study uses a qualitative approach and a type of phenomenological research. Data collection techniques using observation, interviews and documentation. Data analysis techniques are data reduction, data display and conclusion verification. Data validity techniques are triangulation and member checks. The data sources are Educators, Principals and Students. The results of the study are as follows: 1) The stages of implementing visual media in increasing understanding of religious education in children in group A Raudhatul Athfal Aman Sentosa Sekuduk Village, namely: a) The preparatory stage, namely preparing the readiness of educators, students, room arrangement and visual media that will be used properly and appropriately with the topic to be discussed; b) The implementation stage is storing the visual media in the right position, explaining the visual media and the topics discussed and carrying out learning activities together; c) The evaluation stage is conducting question and answer activities between educators and students, direct observation by educators, daily assessments in accordance with the RPPH and carrying out follow-up activities. 2) The obstacle in implementing visual media in increasing understanding of religious education in children in group A Raudhatul Athfal Aman Sentosa Sekuduk Village is that not all educators are able to create and use visual media creatively so that there are students who are less interested in participating in learning activities and the conditions of students which is not conducive. 3) The teacher's efforts to overcome obstacles to the implementation of visual media in increasing understanding of religious education in children in group A Raudhatul Athfal Aman Sentosa Sekuduk Village are always practicing in making and using visual media, establishing collaboration between educators both from within the school and educators from other schools and using several types of visual media and methods in learning activities.